2013
DOI: 10.5455/vetworld.2013.516-520
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic studies of meloxicam after its intravenous administration in local goat (Capra hircus) of Assam

Abstract: Aim: The aim of the present study was to determine the meloxicam concentrations in the plasma of goats at different time intervals after its administration by IV route and data were used to determine the different pharmacokinetic parameters and the bioavailability of meloxicam in goats. Materials and Methods:The present study was conducted on 12 to 18 months old, five adult male local goats (Capra hircus) of Assam, with body weight ranging between 10 to 18 kg. All goats were clinically sound and healthy and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
(1 reference statement)
1
8
2
Order By: Relevance
“…1,7 Meloxicam is a COX-2 selective NSAID that has been used extensively for its anti-inflammatory, analgesic, and antipyretic activity in some domestic animal species. [8][9][10][11] The pharmacokinetics of meloxicam has been evaluated in several species, including baboons, a mice, a horses, 12,13 donkeys, 13 sheep, 14,15 goats, 14,16,17 cattle, 18,19 dogs, 20,21,a vultures, 22 green iguanas, 23 cats, 24,25 piglets, 26,a camels, 27 llamas, 28 and rabbits. [29][30][31] Because no data are available for red-eared slider turtles (Trachemys scripta elegans), the dosage of meloxicam used in that species is routinely extrapolated from dosages for other species (ie, 0.1 to 0.2 mg/ kg, q 24 to 48 h).…”
Section: Aucmentioning
confidence: 99%
“…1,7 Meloxicam is a COX-2 selective NSAID that has been used extensively for its anti-inflammatory, analgesic, and antipyretic activity in some domestic animal species. [8][9][10][11] The pharmacokinetics of meloxicam has been evaluated in several species, including baboons, a mice, a horses, 12,13 donkeys, 13 sheep, 14,15 goats, 14,16,17 cattle, 18,19 dogs, 20,21,a vultures, 22 green iguanas, 23 cats, 24,25 piglets, 26,a camels, 27 llamas, 28 and rabbits. [29][30][31] Because no data are available for red-eared slider turtles (Trachemys scripta elegans), the dosage of meloxicam used in that species is routinely extrapolated from dosages for other species (ie, 0.1 to 0.2 mg/ kg, q 24 to 48 h).…”
Section: Aucmentioning
confidence: 99%
“…In Canada, the use of meloxicam at an oral dose of 1 mg/kg in castration has been approved (Melendez et al., 2019). The dose of meloxicam recommended by European Medicines Agency (EMA) for use in goats is 0.5 mg/kg, whereas some studies have recommended the dose of 1 mg/kg (CVMP, 2006; Wani, Roy, Ashraf, & Roy, 2013). Meloxicam at doses of 1 and 2 mg/kg is quite effective in a sheep inflammation model (Colditz, Paull, Lloyd, Johnston, & Small, 2019; Woodland et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The minimum plasma concentration of meloxicam required for therapeutic effect in goats is 0.07 μg/ml (Wani et al, 2013). The effective plasma concentration (EC 50 ) of meloxicam for antipyretic and analgesic effects is 0.21 and 0.39 μg/ml, respectively, in the paw inflammation model in dogs and that for stride length and lameness are 0.13 and 0.2 μg/ml, respectively, in the arthritis model in horses (Jeunesse et al., 2011; Toutain & Cester, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There were few data reported in the literature regarding the intramuscular administration route of MEL in pigs, but studies have been carried out on the pharmacokinetics of MEL via intravenous administration extensively, and results showed that the t 1/2λz of MEL in plasma were 2.7 hr (0.4 mg/kg) in pigs (Fosse et al, ); 20.35 hr (0.5 mg/kg) and 21.86 hr (0.5 mg/kg) in calves (Coetzee, Kukanich, Kukanich, Mosher, & Allen, ; Coetzee et al, ); 5.29 hr (0.5 mg/kg) in horses (Pierre‐Louis & Cester, ); 8.08 hr (1 mg/kg), 6.73 hr (0.5 mg/kg), and 9.96 hr (0.5 mg/kg) in goats (De Vito et al, ; Shukla et al, ; Wani, Roy, Roy, Ashraf, & Roy, ); 11.54 hr (0.1 mg/kg) in beagle dogs (Junyi Hao & Cao, ); 3. 69 hr (1.5 mg/kg) in guinea pigs (Moeremans, Devreese, Devreese, Baere, Croubels, & Hermans, ); and 6.41 hr (10 mg/kg) in mice (Busch et al, ), revealing great interspecific variability.…”
Section: Discussionmentioning
confidence: 99%
“…(1 mg/kg), 6.73 hr (0.5 mg/kg), and 9.96 hr (0.5 mg/kg) in goats (De Vito et al, 2018;Shukla et al, 2007;Wani, Roy, Roy, Ashraf, & Roy, 2013); 11.54 hr (0.1 mg/kg) in beagle dogs (Junyi Hao & Cao, 2017);…”
Section: Uplc-ms/ms On Account Of the Low Mel Plasma Concentrationsmentioning
confidence: 99%